(untitled) (Clinics, 2013)
Azoospermia is a descriptive term referring to ejaculates that lack spermatozoa without implying a specific underlying cause. The traditional definition of azoospermia is ambiguous, which has ramifications on the diagnostic criteria. This issue is further compounded by the apparent overlap between the definitions of oligospermia and azoospermia. The reliable diagnosis of the absence of spermatozoa in a semen sample is an important criterion not only for diagnosing male infertility but also for ascertaining the success of a vasectomy and for determining the efficacy of hormonal contraception. There appears to be different levels of rigor in diagnosing azoospermia in different clinical situations, which highlights the conflict between scientific research and clinical practice in defining azoospermia.